EDUKASI DAN PENDAMPINGAN DAPAT MENINGKATKAN PENGETAHUAN IBU HAMIL TENTANG SELF-CARE - Kamsatun Kamsatun; Gurid Pramintarto Eko Mulyo; Mustofa Kamil; Iip Saripah (Poltekkes Kemenkes Bandung, 2025)
Limited access to health services, such as minimal prenatal class programs, often increases health risks due to lack of adequate monitoring. In addition, low support from health workers can cause various problems, both physical and psychological, for pregnant women. Poor physical health and high levels of anxiety can have a negative impact on the health of the mother and fetus, even risking the baby being neglected and lacking breast milk. Therefore, when health worker resources are limited, empowering pregnant women becomes very important. The study aimed to analyze the effectiveness of education and assistance in increasing pregnant women's knowledge about self-care in pregnancy. This study used a quasi-experiment with a pre-posttest two group design. The population was pregnant women and the sampling technique was a purposive sampling technique. The number of samples was 60 people divided into two groups. Education and assistance were carried out for approximately 30 minutes, twice with a time span of one week. The media used was a Module. The pre-test was conducted to determine knowledge using a questionnaire. The post-test was conducted in the same way, after intervention was given to both the treatment and control groups. To see the effect of education and assistance, an independent T test was used. The results of the study showed that education and assistance were effective in increasing pregnant women's knowledge about self-care during pregnancy with a p-value of 0.000. The conclusion is that education and assistance are effective in increasing knowledge about self-care during pregnancy.